Analisis Pertumbuhan Ekonomi Regional Melalui Industri Kreatif: Studi Kasus Provinsi Sumatera Barat dengan Pendekatan Time Series - Aisyah, Hesty; Wefielananda, Rahmi Afzhi; Alfajri, Refo; Kamal, Luthfi Ariq (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2025)
The main focus is to assess the contribution of various creative industry sub-sectors to the Gross Domestic Product of West Sumatera from 2014 to 2023. Employing a quantitative method with time series statistical analysis, the study seeks to identify growth patterns and fluctuations in the sector's contribution to regional economic development. The research utilizes secondary data sourced from the Central Statistics Agency (BPS) and annual reports from relevant provincial agencies. The findings are expected to illustrate the creative industry’s contribution to economic growth and highlight the sub-sectors with the greatest impact in strengthening a sustainable creative economy ecosystem. Moreover, the study aims to provide a scientific foundation for local governments in formulating more inclusive economic transformation strategies that align with local cultural strengths and adapt to developments in the digital era.